A high resolution map of mammalian X chromosome fragile regions assessed by large-scale comparative genomics (2014)
Chromosomal evolution involves multiple changes at structural and numerical levels. These changes, which are related to the variation of the gene number and their location, can be tracked by the identification of syntenic blocks (SB). First reports proposed that ~180–280 SB might be shared by mouse and human species. More recently, further studies including additional genomes have identified up to ~1,400 SB during the evolution of eutherian species. A considerable number of studies regarding the X chromosome’s structure and evolution have been undertaken because of its extraordinary biological impact on reproductive fitness and speciation. Some have identified evolutionary breakpoint regions and fragile sites at specific locations in the human X chromosome. However, mapping these regions to date has involved using low-to-moderate resolution techniques. Such scenario might be related to underestimating their total number and giving an inaccurate location. The present study included using a combination of bioinformatics methods for identifying, at base-pair level, chromosomal rearrangements occurring during X chromosome evolution in 13 mammalian species. A comparative technique using four different algorithms was used for optimizing the detection of hotspot regions in the human X chromosome. We identified a significant interspecific variation in SB size which was related to genetic information gain regarding the human X chromosome. We found that human hotspot regions were enriched by LINE-1 and Alu transposable elements, which may have led to intraspecific chromosome rearrangement events. New fragile regions located in the human X chromosome have also been postulated. We estimate that the high resolution map of X chromosome fragile sites presented here constitutes useful data concerning future studies on mammalian evolution and human disease. © 2014, Springer Science+Business Media New York.